Tribodynamic studies of textured gearsets lubricated with fresh and MoS2 blended greases. (January 2022) - Gupta, Niharika; Tandon, N.; Pandey, R.K.; Vidyasagar, K.E. Ch.; Kalyanasundaram, Dinesh
Abstract: The synergistic effects of surface texture and Molybdenum disulphide (MoS2 ) blended grease have been explored on the tribodynamic performance of spur gearsets. A texture involving ellipsoidal dimples on the face and flank of pinions' teeth was fabricated using nanosecond pulsed fiber laser. The experiments were performed at different applied torques and a pitch line velocity of 4 m/s keeping in mind the practical application of the results. Contact resistance, vibrations, temperature rise and surface topographies have been measured and analyzed. Substantial increase (about 300%) in contact resistance and reduction (40% approximately) in vibration amplitudes at gear mesh frequency were found in the presence of texture. Reduction in interfacial temperature rise and less damage to teeth surface were also observed. Highlights: Tribodyamic studies of textured spur gearsets involving the ellipsoidal dimples using fresh and molybdenum disulphide (MoS2 ) blended greases. The contact resistance increased up to 300% in the presence of dimples in texture. Substantial reductions of 40% in vibration amplitudes in the presence of textured pinion and MoS2 blended grease. About 15 °C temperature reduction in the presence of dimples and MoS2 blended grease.